I Lost It at the Movies : Parodic Spectatorship in Hector Babenco’s Kiss of the Spider Woman - Williams, Bruce (Cinémas)

(untitled) (Cinémas, 1999)
ABSTRACTAn international coproduction representative of the post-Cinema novo mainstream, Hector Babenco's Kiss of the Spider Woman reassesses the Brazilian notion of cultural anthropophagy to examine the subversion of spectatorial identification. While anthropophagy, as envisioned by Oswald de Andrade, the most radical of Brazilian Modernists, consumes metropolitan culture, Babenco's film foregrounds the consumption and reprocessing of images. Through exaggeration and camp, the reconfiguration of a propaganda film parodies classical spectatorship and opens doors to negotiated readings of film. Babencos film offers a contestatory reading of another's cultural icon, redeploying propaganda to decry the plight of the disenfranchised and the political repression of the Southern Cone.